2017
DOI: 10.1186/s13031-017-0103-3
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and trauma in asylum seekers landing in Sicily in 2015: a descriptive study of neglected invisible wounds

Abstract: BackgroundIn 2015, Italy was the second most common point of entry for asylum seekers into Europe after Greece. The vast majority embarked from war-torn Libya; 80,000 people claimed asylum that year. Their medical conditions were assessed on arrival but their mental health needs were not addressed in any way, despite the likelihood of serious trauma before and during migration. Médecins sans Frontières (MSF), in agreement with the Italian Ministry of Health, provided mental health (MH) assessment and care for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 22 publications
2
87
0
1
Order By: Relevance
“…A German study found an association between depressive symptoms and migration status in the older migrant populations (19). A more recent study described the mental health condition of asylum seekers who passed through Médecins sans Frontières clinics in Sicily between October 2014 and December 2015 and, when invited, presented themselves for mental health screening (20). Of the 385 who were screened, most were young men who had left their home countries in West Africa more than a year prior to arrival.…”
Section: Mental Health In Adult Refugees and Migrantsmentioning
confidence: 99%
“…A German study found an association between depressive symptoms and migration status in the older migrant populations (19). A more recent study described the mental health condition of asylum seekers who passed through Médecins sans Frontières clinics in Sicily between October 2014 and December 2015 and, when invited, presented themselves for mental health screening (20). Of the 385 who were screened, most were young men who had left their home countries in West Africa more than a year prior to arrival.…”
Section: Mental Health In Adult Refugees and Migrantsmentioning
confidence: 99%
“…A German study found an association between depressive symptoms and migration status in the older migrant populations (18). A more recent study described the mental health condition of asylum seekers who passed through Médecins sans Frontières clinics in Sicily between October 2014 and December 2015 and, when invited, presented themselves for mental health screening (19). Of the 385 who were screened, most were young men who had left their home countries in West Africa more than a year prior to arrival.…”
Section: Mental Health In Adult Refugees and Migrantsmentioning
confidence: 99%
“…The most common mental health conditions were post-traumatic stress disorder (31%) and depression (20%). Most of the potentially traumatic events were reported to have been experienced in the home country (60%) and during the journey (89%), but the trauma of being a refugee was also reported, with activity deprivation, worries about people who were left behind, loneliness and fears of being sent back (19).…”
Section: Mental Health In Adult Refugees and Migrantsmentioning
confidence: 99%
“…The camp nurse told me that all of them should go to therapy, but there are no funds and communication is limited (they do not speak Italian). This information is confirmed by the data provided by physicians working with the asylum seekers (Nosè et al 2017;Crepet et al 2017). For this reason, I have decided that traumatic and difficult issues will constitute a minuscule part of our conversations and that the movies will consist mostly of comedies.…”
Section: Methodsology: Conducting Field Research In the Campmentioning
confidence: 71%
“…16 Two main French charity organizations -the frame for the medical help. 17 The most often we can find the studies analyzing such topics as the health or the mental health of the refugees (Cernovsky 1988;Brown, Schale, Nilsson 2010;Crepet et al 2017;Centre Primo Levi 2018). 18 This is probably the most often researchers (even those who are mentioning the field study and ethnography) are working based on the interviews with the volunteers.…”
Section: Unusual State Of Artmentioning
confidence: 99%